Envisioning the Future of Learning for Creativity, Innovation and Entrepreneurship - Kyriaki Papageorgiou; Olga Kokshagina (Envisioning the Future of Learning for Creativity, Innovation and Entrepreneurship, 2022)
Envisioning the Future of Learning for Creativity, Innovation and Entrepreneurship outlines the work and findings of the Erasmus+ VISION research project. Education is changing and teachers and students around the world are reshaping it. This book is designed to help educators, policy makers and stakeholders from industry and society at large navigate the changing landscape of education for creativity, innovation, and entrepreneurship (CIE). Built on insights from more than 250 experts, the book presents a learning landscape that captures today's shifts within CIE education and proposes guidance and potential pathways for those involved in the field. The book shows that the landscape of education for CIE is influenced by: Learning as an immersive experience driven by play and experimentation The rise in on the job education and learning by doing as part of life-long upskilling Teachers' roles evolve to be coaches and mentors developing hard and soft skills Numerous images are included in the book using the technique of visual thinking, stimulating imagination, creativity and innovation
10.1515/9783110752205; 10.1515/9783110752205